👤
a fost răspuns

(x-1)²-(2x+1)²-6=2(5-x)-3x(x+1)-23

X12x1625x3xx123 class=

Răspuns :

X la a doua = y P'S nu stiu cum sa pun de pe tel X la a doua :( y+1-2x-4y-1-4x = -13-5x -3y -3y-6-6x = -13-5x -3y -3y+ 3y -6x +5x = -13×6 -× =7 | ( -1) X = -7
                 
[tex]\text{Este o ecuatie de gradul 2 reductibila la gradul 1} \\ (x-1)^{2}-(2x+1)^{2}-6=2(5-x)-3x(x+1)-23 \\ ( x^{2} -2x+1)-(4 x^{2} +4x+1)-6=(10-2x)-(3x^{2}+3x)-23 \\ x^{2} -2x+1-4 x^{2} -4x-1-6=10-2x-3x^{2}-3x-23 \\ -3x^{2} -6x-6=-3x^{2}-5x-13 \\ -3x^{2} +3x^{2}-6x+5x-6+13=0 \\ -x+7=0\;\;\;\;\;\;|*(-1) \\ x-7=0 \\ x=\boxed{7}[/tex]